Efficiency of Trichogramma exiguum Pinto & Platner and T. pretiosum Riley to control Argyrotaenia sphaleropa (Meyrick) y Bonagota cranaodes (Meyrick) in Uruguayan vineyard - Basso, C.; Grille, G.; Pintureau, B. (Agrociencia Uruguay, 1999)
Toe efficiency of Trichogramma exiguum and T. pretiosum to control the main Uruguayan vineyard pests, Argyrotaenia sphaleropa and Bonagota cranaodes, was tested by means of releases (350,000 Trichogramma females/ha) during the beginning of the second flight of the second pest generation. The percentage of parasitism was null before releases, both treated plots and in a non-treated plot ( control). Toe parasitism of the two Tortricidae species caused by released T. exiguum reached 20% during the first field generation of the parasitoid, 53.8% during the second generation, and 75% during the third generation. Toe parasitism caused by T. pretiosum reached 14.6, 45.1 and 82.5 respectively during the first, second and third generations. In the non-treated plot, parasitized egg-masses were only observed in the two last samples collected. The species T. exiguum caused a higher percentage of parasitism on B. cranaodes than T. pretiosum. The two Trichogramma species showed a similar efficiency to parasitize A. sphaleropa. At the end of the experiment, most of the A. sphaleropa and B. cranaodes eggmasses were localized on the upper part of the vine plants. The A. sphaleropa egg-mass localization wás only influenced by the parasitism of T. exiguum, which was higher in the upper part of plants than in the lower part. In the field, the parasitism efficiency seems lower in T. pretiosum than in T. exiguum since the first species was be excluded from a plot by the second species after its release. Therefore, T. exiguum seems the most efficient species to control the leaf rollers in vineyards.